A review on iron chelators as potential therapeutic agents for the treatment of Alzheimer’s and Parkinson’s diseases - Singh Y.P.; Pandey A.; Vishwakarma S.; Modi G. (My University, 2025)
Iron plays a vital role in several cellular functions due to its unique physiochemical properties. Iron concentration increases in the brain with age due to multiple factors. Excessive amount of iron can lead to formation of reactive oxygen species. Neurodegenerative disorders are characterized by iron supplemented increase in oxidative stress and cellular damage. There is an urgent need of novel therapies which should not only provide symptomatic relief but also be able to modulate iron accumulation in the brain. Therefore, the development of novel iron chelators as neuroprotective agents for the treatment of neurodegeneration is an emerging trend. Several iron chelators including 8-hydroxyquinoline derivatives, dopaminergic agonists and natural products are under preclinical and clinical investigations for the treatment of neurodegenerative disorders. © 2018, Springer Nature Switzerland AG.